The Right to Life Denied: The Culture of Violence along the Us-Mexican Border - Kaczmarek, Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
With a focus on Ed Vulliamy's “Amexica: War Along the Borderline” (2010), the outcome of the author's field research in the American-Mexican borderlands, the article aims to present the progressive brutalization of the border's public life. Discussing the quantitative and qualitative scale of violence in Mexico, it explains the main reasons for the escalation of bloodshed, attributable, among other things, to cartels, which function in a similar way to legal international corporations. The article also exemplifies how drug trafficking organizations shape the culture of violence in public space, discourse, entertainment, and education. In addition, the purpose of this paper is to show that to a certain extent the United States is co-responsible for the flourishing culture of violence there, which clearly affects not only its southern neighbor, but also American citizens.
Keywords: Vulliamy; Amexica; American-Mexican border; cartel; violence